2013
DOI: 10.5688/ajpe778163
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles and Teaching Perspectives of Canadian Pharmacy Practice Residents and Faculty Preceptors

Abstract: Objective. To characterize and compare learning styles of pharmacy practice residents and their faculty preceptors, and identify teaching perspectives of faculty preceptors. Methods. Twenty-nine pharmacy residents and 306 pharmacy faculty members in British Columbia were invited to complete the Pharmacists' Inventory of Learning Styles (PILS). Faculty preceptors also were asked to complete the Teaching Perspectives Inventory (TPI). Results. One hundred percent of residents and 61% of faculty members completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…This resembles results from our previous study, which showed the distribution of learning style was identical between residents and their preceptors, who were both dominated by passive/abstract learning styles. 12 Our results contrast with those of medical residents, whose learning style shifted toward the more active assimilator or converger styles during the course of their training. 13 While most former residents found their learning style assessment to be useful, few adjusted their learning or practice habits as a result.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This resembles results from our previous study, which showed the distribution of learning style was identical between residents and their preceptors, who were both dominated by passive/abstract learning styles. 12 Our results contrast with those of medical residents, whose learning style shifted toward the more active assimilator or converger styles during the course of their training. 13 While most former residents found their learning style assessment to be useful, few adjusted their learning or practice habits as a result.…”
Section: Discussioncontrasting
confidence: 55%
“…12 Clearly, learning style does change in this period, but likely within the bounds of behaviors and preferences demonstrated by peers, preceptors, colleagues, and mentors. The demonstrated early-career lability of learning preferences may indicate an opportunity for residency programs and mentors to focus on coaxing learning preferences toward the active and concrete.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24,[128][129][130][131] Research in pharmacy students or residents has derived from limited studies: seven American cohorts, 23,130,128,129,[131][132][133] one Canadian, 134 and one Australian cohort. 24 Furthermore, one of the American studies involved research from more than 30 years ago.…”
Section: Pharmacy Research In Learning Stylesmentioning
confidence: 99%